Redescription and new records of Synopia ultramarina Dana (Amphipoda: Synopiidae) from off the northeastern Brazil, with comments on its morphological variations - Senna,André R. (2020)
ABSTRACT Synopia ultramarina Dana, 1853 is considered a circumtropical species and was originally described based on material collected from two localities near halfway between the southwestern Africa and northeastern Brazil. The species is redescribed here with samples from Fernando de Noronha Archipelago, Pernambuco state, northeastern Brazil. The material examined was collected by SCUBA diving, from rhodolith beds, in Ressureta Channel, between Meio and Rata Islands. Additional material was collected from off Ceará state coast, during environmental consultancies, by Petrobras S. A., and off Pernambuco state coast, during the Project REVIZEE NE IV. Discussion on morphological variations of the species is presented, based on the studied material and previous descriptions in the literature.